TOWARDS KINETIC REGIME OF REVERSE FLOW OPERATION - Yogi Budhi (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2005)
An analysis of reverse flow operation and its experimental study for ammonia oxidation to produce either N2, N2O, and NO have been carried out. An experimental set-up of reverse flow reactor was constructed for a laboratory scale. The experiment under steady state operation was performed as a base case in order to judge the potential during the reverse flow operation. Aim was to investigate the behavior of reverse flow operation and to observe the reactor performance. Focus was on the comparison of the steady state and reverse flow operations. The experiments show that the behavior of reverse flow reactor is strongly influenced by the ratio of the switching time over the residence time. The ammonia conversion during the regular reverse flow operation shows lower values compared to the steady state operation which is even worse during asymmetric mode. The product distributions may change under flow reversal, depending on the operating conditions, regime of operation, and operation mode.Keywords : Reverse Flow Operation, Fixed Bed Reactor, Selectivity Manipulation, Steady State Operation, Ammonia OxidationAbstrak Sebuah analisis operasi aliran bolak-balik dan studi eksperimental oksidasi amoniak untuk menghasilkan baik N2., N2O, dan NO telah dilakukan. Sebuah perangkat eksperimen reaktor aliran bolak-balik dikonstruksi untuk skala laboratorium. Eksperimen dalam operasi keadaan tunak dilakukan sebagai kasus dasar untuk menilai potensi operasi aliran bolak-balik. Tujuan penelitian ini adalah untuk meneliti kelakuan operasi aliran bolak-balik dan untuk mengamati kinerja reaktor. Kajian ini dititikberatkan pada perbandingan operasi keadaan tunak dan operasi aliran bolak-balik. Hasil percobaan menunjukkan bahwa kelakuan reaktor aliran bolak-balik sangat dipengaruhi oleh nisbah waktu pembalikan arah aliran (switching time) terhadap waktu tinggal. Konversi amomiak dalam operasi aliran bolak-balik menunjukkan nilai yang lebih rendah dibandingkan dengan operasi keadaan tunak dan dalam mode asimetrik konversinya bahkan lebih rendah lagi. Distribusi produk dapat berubah dalam pembalikan aliran yang bergantung pada kondisi-kondisi operasi, daerah operasi, dan mode operasi.Kata Kunci : Operasi Aliran Bolak-balik, Reaktor Fixed Bed, Manipulasi Selektivitas, Operasi Tunak, Oksidasi Amoniak